Health System Capacity to Deliver Routine Childhood Immunisations: An Assessment of Health Facilities in Gazelle and Kokopo Districts, East New Britain - Milena Dalton; Stefanie Vaccher; Christopher Morgan; Benjamin Sanderson; Pele Melepia; Hannah A. James; Lynette Duwaba; Benjamin Paivu; Patrick Kiromat; Elsie Stanley; Edward Waramin; Moses Laman; et al. (Vaccines, 2026)
Background: Over the past decade, the East New Britain Provincial Health Authority in Papua New Guinea has worked with partner research organisations to implement data-driven interventions to improve immunisation coverage. This paper reports on facility assessments conducted as part of a cross-sectional study to understand improvements and identify enablers and barriers to routine childhood immunisation in the province. Methods: Between May and August 2023, nine urban and rural health facilities, providing immunisation services at the time of the study in five areas, were assessed using an adapted World Health Organisation (WHO) Service Availability and Readiness Assessment tool. The tool evaluated facility characteristics, routine childhood immunisation readiness and vaccine supply data. Data were analysed using descriptive statistics and findings were mapped to adapted WHO health system categories to identify service delivery improvement priorities. Findings: Several aspects of immunisation service availability and quality had improved since an assessment in 2016/17. Strengths included fixed-facility and outreach service models tailored to catchment populations, high availability of cold chain and vaccine administration equipment, improved immunisation guidance and job-aids. Priority areas included increasing workforce capacity, improving health record completion to inform outreach, increasing availability of guidelines and reporting tools, reducing stock-outs and enhancing stock tracking. Conclusions: Offering accessible vaccination at every opportunity and using quality data to inform programme implementation and resource allocation are priorities for the Provincial Health Authority. This facility-level assessment identified existing immunisation delivery strengths and highlighted community- and provincial-level priority investment areas to strengthen facility capacity and routine immunisation service delivery.